Nanoparticle-Assisted Diagnosis and Treatment for Abdominal Aortic Aneurysm - Yin, Li; Zhang, Kaijie; Sun, Yuting; Liu, Zhenjie (Frontiers in Medicine, 2021)
An abdominal aortic aneurysm is a localized dilatation of the aorta related to the regional weakening of the wall structure, resulting in substantial morbidity and mortality when the aortic ruptures as complications. Ruptured AAA is a dramatic catastrophe, and aortic emergencies constitute one of the leading causes of acute death in older adults. AAA management has been centered on surgical repair of larger aneurysms to mitigate the risks of rupture, and curative early diagnosis and effective pharmacological treatments for this condition are still lacking. Nanoscience provided a possibility of more targeting imaging and drug delivery system. Multifunctional Nanoparticles (NPs) may be modified with ligands or biomembranes to target agents' delivery to the lesion site, thus reducing systemic toxicity.Furthermore, NPs can improve drug solubility, circulation time, bioavailability, and efficacy after systemic administration. Judiciously engineered The varied nano-bio materials can exist stably in the blood vessels for a long time without being taken up by cells. Here in this review, we focused on the nanoparticles application in imaging and treatment of AAA. We hope to make an overview of NP-assisted diagnose and therapy in AAA and discussed the potential of NP-assisted treatment